“Nunca é feminista o suficiente”: mulheres e feminismos na Igreja Evangélica de Confissão Luterana no Brasil - Pires, Joyce Aparecida [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Considerando o período de 40 anos de abertura para a participação das mulheres na estrutura eclesiástica da Igreja Evangélica de Confissão Luterana no Brasil (IECLB), esta pesquisa pautou-se no estudo da dinâmica dos processos históricos e sociais que reconfiguram as experiências religiosas e ressignificam as práticas das mulheres cristãs de confissão luterana como autoridades eclesiásticas. Fundada como Igreja evangélica no Brasil pelos imigrantes europeus protestantes, tem se desenvolvido como uma Igreja “atuante” no Brasil. Utilizou-se a produção de depoimentos escritos, fontes orais e a etnografia multissituada, em São Paulo e no Rio Grande do Sul. Existe um impacto dos feminismos nas subjetividades das mulheres envolvidas na elaboração e difusão de um ideário feminista espiritualista com incidência nos contextos político, religioso e de ensino no Brasil. Conclui-se que o ideário feminista, por meio da teologia feminista, no contexto da confessionalidade luterana, atende melhor as mulheres neste mundo religioso.

Considering the 40 years of openness to female participation in the ecclesiastical structure of the Evangelical Church of Lutheran Confession in Brazil (IECLB), this research started from the study of the dynamics of historical and social processes that reconfigure religious experiences and reframe the practices of Christian women of confession Lutheran as ecclesiastical authorities. Founded as an evangelical church in Brazil by Protestant European immigrants, it has become an “active” church in Brazil. The production of written testimonies, oral sources and multi-sited ethnography in São Paulo and Rio Grande do Sul were used. There is an impact of feminism on the subjectivities of the women involved in the elaboration and dissemination of a spiritist feminist ideology with an impact on the political, religious and pedagogical contexts in Brazil. It is concluded that feminist ideology, through feminist theology, in the context of Lutheran confessionality, better serves women in this religious world.
“Never feminist enough”: women and feminisms in the Evangelical Church of Lutheran Confession in Brazil
Keywords: Feminismo; Igreja luterana; Mulheres; Religião; Teologia feminista; Feminism; Evangelical church; Women; Religion; Feminist theology